TRIPS flexibilities and TRIPS-plus provisions in the RCEP chapter on intellectual property: How much policy space is retained? - Vitor Henrique Pinto Ido (South Centre, 2021)
The Regional Comprehensive Economic Partnership (RCEP) was signed on 15 November 2020 by 15 Asian-Pacific countries (ASEAN-Brunei Darussalam, Cambodia, Indonesia, Laos, Malaysia, Myanmar, Philippines, Singapore, Thailand, and Vietnam-, and China, Japan, South Korea, Australia and New Zealand), comprising about one third of the world's population and economy. India was a crucial party to the negotiations but opted out of the agreement. Ratification of the agreement is still pending, subject to more Parties ratifying it at the national level. This paper provides a broad overview of the RCEP agreement and discusses the details of the intellectual property (IP) Chapter. Significantly, it does not contain substantive TRIPS-plus provisions that undermine public health in developing countries-although it does contain such provisions in other areas such as copyrights, trademarks, and IP enforcement.
Keywords: 300; Access to Knowledge; Access to Medicines; Association of Southeast Asian Nations (ASEAN); Competition; Cooperation; Copyright; Country Names; COVID-19; Flexibilities; Genetic Resources; Geographical Indications; Industrial Designs; Intellectual Property; IP Enforcement; Patent; Procedural Matters; Public Health; Regional Comprehensive Economic Partnership (RCEP); Technical Assistance; Technology Transfer; Trademarks; Traditional Knowledge; Transition Period; Transparency; TRIPS; TRIPS Plus